Giant Cell Tumor of Lower End of Tibia - Monish Bami; Ashok R. Nayak; Shreepad Kulkarni; Avinash Kulkarni; Rupali Gupta (Case Reports in Orthopedics)
Introduction. Giant cell tumor of bones is an unusual neoplasm that accounts for 4% of all primary tumors of bone, and it represents about 10% of malignant primary bone tumors with its different grades from borderline to high grade malignancy. Case Report. A 35-year-old patient presented with complains of pain and swelling in left ankle since 1 year following a twisting injury to his left ankle. On examination, swelling was present over the distal and anterior part of leg and movements of ankle joint were normal. All routine blood investigations were normal. X-ray and CT ankle showed morphology of subarticular well-defined expansile lytic lesion in lower end of left tibia suggestive of giant cell tumor. Histopathology of the tissue shows multinucleated giant cells with uniform vesicular nucleus and mononuclear cells which are spindle shaped with uniform vesicular nucleus suggestive of GCT. The patient was treated by excision, curettage, and bone cement to fill the defect. Conclusion. The patient at 12-month followup is doing well and walking without any pain comfortably and with full range of motion at ankle joint with articular congruity maintained and no signs of recurrences.